States’ Obligations on Climate Change: Reviewing the ICJ 2025 Advisory Opinion - Nirodha, T. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Climate change poses an existential threat to humanity, disproportionately affecting coastal and Small Island Developing States. The International Court of Justice’s (ICJ) 2025 advisory opinion on climate change marks a transformative moment in international environmental law, clarifying the binding legal obligations of states to prevent, mitigate, and remedy climate harm, following a request from the UN General Assembly to address two key questions: what are the states’ obligations regarding climate change, and what are the legal consequences if they fail to meet these obligations. In addressing these questions, the ICJ highlighted five main areas of state responsibility: obligations under climate treaties such as the UNFCCC, Kyoto Protocol, and Paris Agreement, customary international law, environmental treaties, law of the sea, and international human rights law. This article critically examines the implications of the ICJ advisory opinion for South Asian coastal states, including the Maldives and Sri Lanka, which are highly vulnerable to sealevel rise, coastal erosion, and extreme weather events. It focuses on the sociolegal consequences of forced displacement, loss of territory, and the governance of maritime resources, assessing how states can fulfil their international obligations. Using a doctrinal and comparative legal analysis, the study reviews the ICJ opinion alongside relevant international treaties, customary international law, environmental agreements, UNCLOS, and human rights frameworks. The ICJ’s recognition of the presumption of continuity of statehood despite physical submergence provides a crucial safeguard for small island states, representing a significant shift from traditional customary and treaty-based international law on statehood. The opinion underscores states’ obligations to exercise due diligence, regulate private actors, cooperate internationally, provide climate finance, and implement comprehensive national and regional strategies. The article concludes that the ICJ’s advisory opinion gives South Asian countries moral strength and legal clarity. However, effective implementation requires proactive planning, cooperation, and engagement of leaders, policymakers, scholars, and communities to ensure that coastal regions remain resilient, stable, and dignified in the face of climate challenges, including forced displacement, loss of territory, and maritime resource management.
Keywords: Climate change; ICJ advisory opinion; South asian coastal states; Human rights; Continued statehood